Peran Kepuasan Pelanggan Dalam Memediasi Hubungan Pengalaman Berbelanja Secara Online Dengan Perilaku Pasca Pembelian - Sumartini, Ade Ruly; Giantari, I Gusti Ayu Ketut; Setiawan, Putu Yudi (Jurnal Ekonomi Kuantitatif Terapan, 2018)
The development of internet has led an increasing presence of online store, followed by developments in online shopping activities. The purpose of this study is to explain the role of customer satisfaction in mediating the relationship between experiences by word of mouth as well as the repurchase intention. The sample are 140 people in Denpasar who purchased cosmetics through online shop at least 1 times in the last of 6 month, determined using purposive sampling method. This research uses PLS (Partial Least Square) analysis. The study showed that online shopping experience has a positive and significant impact on customer’s satisfaction, repurchase intention and positive word of mouth. Customer’s satisfaction has a positive and significant effect on repurchase intention and positive word of mouth. Customer’s satisfaction was also shown has mediation effect on repurchase intention and positive word of mouth.